2019
DOI: 10.1093/mnras/stz1188
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian-mixture-model-based cluster analysis of gamma-ray bursts in the BATSE catalog

Abstract: Clustering is an important tool to describe gamma-ray bursts (GRBs). We analyzed the Final BATSE Catalog using Gaussian-mixture-models-based clustering methods for six variables (durations, peak flux, total fluence and spectral hardness ratios) that contain information on clustering. Our analysis found that the five kinds of GRBs previously found by other authors are only the cut groups of the previously well-known three types (short, long and intermediate in duration). The two short and intermediate duration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 53 publications
(72 reference statements)
0
16
0
1
Order By: Relevance
“…spanned by the PCs, up to a four-dimensional log T 90 − log F tot − log H 32 − log P 256 instance (see Table 1). The six-dimensional case (Mukherjee et al 1998;Chattopadhyay & Maitra 2017;Tóth et al 2019), i.e. with added T 50 and H 321 , was not taken into account due to very high correlations (r > 0.96) between T 90 and T 50 , and between H 32 and H 321 .…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…spanned by the PCs, up to a four-dimensional log T 90 − log F tot − log H 32 − log P 256 instance (see Table 1). The six-dimensional case (Mukherjee et al 1998;Chattopadhyay & Maitra 2017;Tóth et al 2019), i.e. with added T 50 and H 321 , was not taken into account due to very high correlations (r > 0.96) between T 90 and T 50 , and between H 32 and H 321 .…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Most recently, Tóth et al (2019) performed the usual Gaussian mixture modeling of the BATSE catalog, utilizing six variables 4 : T 90 , T 50 , F tot , P 256 , H 32 , and H 321 . They found that this six-dimensional space is best described by five Gaussian components, consistent with (Chattopadhyay & Maitra 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, considering skewed distributions, two-component mixtures have also been indicated (Tarnopolski 2019b,a). In higher-dimensional spaces, things become less unambiguous (Mukherjee et al 1998;Chattopadhyay et al 2007;Chattopadhyay & Maitra 2017Modak et al 2018;Acuner & Ryde 2018;Horváth et al 2019;Tóth et al 2019;Tarnopolski 2019c). For the most recent, detailed overview on the topic of parametric clustering of GRBs, readers can refer to Tarnopolski (2019c).…”
Section: Introductionmentioning
confidence: 99%
“…This generally holds in higherdimensional parameter spaces as well (Tarnopolski 2019b,a,c). It was sometimes noted that the distributions appear skewed, though (e.g., Mukherjee et al 1998;Tóth et al 2019), but such observation was not followed by employing asymmetric models.…”
Section: Introductionmentioning
confidence: 99%